PENGUKURAN KUALITAS HIDUP PASIEN HIPERTENSI DI POLI PENYAKIT DALAM RSUD ULIN BANJARMASIN - Saftia Aryzki; Amaliah Wahyuni (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Hypertension is one of the deadliest diseases in the world. As many as 1 billion people in the world or 1 in 4 adults suffer from this disease. In fact, it is estimated that the number of hypertension sufferers will increase to 1.6 billion by 2025. Measuring the quality of life of hypertensive patients using the Indonesian version of the EQ5D questionnaire. The purpose of this study was to determine the quality of life of hypertensive patients at RSUD Ulin Banjarmasin using the EQ5D instrument. This study is an observational study conducted prospectively. Data were collected by filling out the EQ5D questionnaire by all hypertensive patients at the Internal Medicine Department at Ulin Hospital Banjarmasin. The research sample is part of the population that meets the inclusion and exclusion criteria with the simple random method. The inclusion criteria were patients aged 18-65 years and willing to take part in the study. Meanwhile, the exclusion criteria were pregnant, blind and deaf, only the patient's family and absent at the second visit. This research was conducted at the Internal Medicine Polyclinic of Ulin Hospital from March-June 2020. Based on the research that has been done, it was found that the average value of the quality of life of hypertension patients at Ulin Banjarmasin Hospital, the average value of quality of life was 0.792, with a quality of life value ≥ 0.792 as many as 19 patients (63.33%) in the category of good quality of life and value quality of life ≤ 0.792 as many as 11 patients (36.67%) in the poor quality of life category.